Do intensive services obviate the need for CTOs?. (July 2016) - O'Reilly, Richard; Corring, Deborah; Richard, Julie; Plyley, Cathy; Pallaveshi, Luljeta
Abstract: Objective: Opponents of community treatment orders (CTOs) argue that they would be unnecessary if sufficient community services such as assertive community treatment (ACT) teams were available. This study was designed to determine the frequency of CTO use for patients on ACT teams; reasons why patients receiving ACT services are placed on CTOs; and views of stakeholders on use of CTOs on ACT teams. Methods: We identified all patients on a CTO while being served by ACT teams in London, Ontario, between 2000 and 2013. Data were collected using chart review, questionnaires completed by psychiatrists and focus groups for patients, their relatives and non-psychiatrist clinicians. Results: During the study period, 190 patients were on a CTO while receiving ACT services. In December 2013, 17% of London's ACT team patients had an active CTO. ACT alone had been tried for 57% of patients before a CTO was introduced. Psychiatrists cited refusal of treatment and unavailability for follow-up as the primary reasons why ACT alone was ineffective. Patients were ambivalent about CTOs: describing them as coercive while simultaneously noting benefits. Relatives and non-psychiatrist clinicians were more clearly positive about the use of CTOs. Conclusions: The availability of intensive services does not ensure that patients will engage with those services. Clinical implications: Community legislation requiring some patients to adhere to treatment is needed in addition to intensive clinical services. Limitations: This study conducted in a single location may not generalize to other regions. Many patients were not approached to participate in the focus groups which call into question the representativeness of patient opinions.